Historical and political development of women's participation in Argentina. Continuities and challenge (Papeles, 2023)
This paper presents an overview of how affirmative actions, such as gender quotas and parity laws,  were legislated in Argentina.To begin with, this essay provides a balance on how these laws impacted legislative integration in the National Congress, particularly in the Chamber of Deputies. Secondly, it focuses on the debate and approval of parity laws, considering its context and the fact that there were critical positions. Since that there is still opposition to these policies, it finally examines some potential difficulties for this procedure in the future.
Keywords: Affirmative actions; quota laws; parity; representation; legislative power